EFEKTIFITAS ANTIBAKTERI SENYAWA METABOLIT SEKUNDER PADA BEBERAPA TANAMAN OBAT TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS - Zahki, Muhammad (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Infection is one of the diseases that can be transmitted to humans which until now still has to be seriously resolved. Staphylococcus aureus infection is a problem that is of great concern due to the increase in bacterial resistance to various antibiotics. With the widespread resistance of bacteria to existing drugs, further encouragement must be carried out on the importance of efforts to create new alternatives by administering infectious disease prevention drugs using raw materials from nature. The research method uses secondary data taken from literature studies, which are analyzed from data related to the effectiveness of medical plants. Data collection techniques in this research are in the form of reviews from scientific journals, published national and international journals. The results obtained from several research literatures that are effective against the growth of staphylococcus aureus bacteria are Moringa leaves. Where at low concentrations, Moringa leaves provide a large diameter of the inhibition area for bacterial growth and if the given concentration is increased, the diameter of the area of ​​bacterial inhibition produced will be even greater. This is also supported by several previous studies that have been carried out by many researchers that Moringa leaves have antibacterial activity against antibiotic-resistant pathogenic bacteria, especially Staphylococcus aureus bacteria and Moringa leaves contain several secondary metabolite compounds that actively inhibit bacterial growth, namely flavonoids, saponins and tannins.